CHANGES IN THE WIDTH OF THE PERIODONTAL GAP OF RATS WITH SUPRAOCCLUSAL RELATIONSHIPS OF INDIVIDUAL TEETH IN THE AGE ASPECT - Zviahin, Serhii; Lakhtin, Yurii (Eastern Ukrainian Medical Journal, 2024)
Introduction. The dentoalveolar apparatus is a complex of complicated interaction of the jaws, masticatory muscles, teeth, and temporomandibular joints. This connection is carried out by the trigeminal nerve system with sensory and motor nuclei closely connected to the cortical and subcortical centers of the brain. Occlusal trauma is a lesion that develops in the periodontium as a result of forces that exceed the periodontal potential for functional adaptation. Occlusal trauma can be classified as primary or secondary. The first one occurs in the pulp and periodontal ligament when the force of the action on the dental structures is greater than usual, under optimal periodontal support conditions. It includes orthodontic movements, "high" restorations, and parafunctional habits such as bruxism. Secondary occlusal trauma occurs when the teeth with previous supporting tissue changes are subjected to the action of normal and excessive forces with supporting tissue changes caused by periodontal disease or previous trauma. The available evidence has demonstrated that bacterial plaque bioactive substances lead to local inflammatory responses in periodontal tissues which contribute to bone tissue resorption through osteoclasts in periodontitis. Excessive functional stress can initiate inflammatory changes in the periodontium and thus, increase destructive bacterial processes. Traumatic occlusion can expand the space of the periodontal ligament and in this way stimulate apical bacterial migration and proliferation. However, few attempts have been made to investigate the molecular mechanisms that trigger bone tissue resorption in traumatic occlusion. The analysis of publications on the studies of morphological changes in periodontal tissues in individual teeth supraocclusion in the age aspect shows the contradictory data. The aim: to determine the morphometric changes of the periodontal gap as a component of the periodontal complex in rats of different age groups in the supraocclusal relationship of individual teeth in the age aspect. Materials and methods of the study. The scientific experiment was conducted on 60 white laboratory rats aged 4 to 22 months and weighing 90 to 330 g. The rats were divided into control (30 animals) and experimental (30 animals) groups. Each group was divided into 3 subgroups (10 animals each) depending on the age of the rats: young, mature and senile. Young animals included rats aged 3–4 months with a weight of 90–100 g; mature animals - aged 6–8 months with a weight of 150–170 g; senile rats – 20–22 months and weighing 200–220 g. The method of modelling the state of supraocclusal relations of individual teeth is described in the previous publication. For histological examination of dental blocks, the following was performed. Fixation in a 10% solution of neutral formalin for two days, dehydration in alcohols of increasing concentration and embedding in paraffin. After preparation, sections were made on a Shandon Finesse 325 rotary microtome with a section thickness of 4-6 µm. The histological sections were fixed on pre-degreased slides and dried. Van Gieson staining was performed. The width of the periodontal gap was determined using the ZEISS ZEN 3.7 program by Carl Zeiss Microscopy. For statistical data processing, the AtteStat v.12.5 software was used to determine the mean value and its standard error (M±m). The probability of a statistically significant difference between the data obtained was assessed using the Student’s parametric test (at a significance level of p ≤ 0.05). All samples were tested for normality using the Gupta test. Results of the study. Statistical differences were observed in rats of all groups, as well as between the indicators of all rats of the control and experimental groups (≤0.05). The width of the periodontal gap increased by 34.1% in young rats, by 25.5% in mature rats, and by 21.1% in senile rats. Conclusions The presence of supraocclusal relationships of individual teeth causes an increase in the periodontal gap in rats of all age groups. The greatest expansion of the periodontal gap has occurred in young rats. The width of the periodontal gap in rats decreases with age.